Teachers’ Questions on Students’ Participations A Discourse Analysis in Fourth-Year English Education Program - Maurina, Selvia; Sallama, Mutiara; Dewi, Sinta (English Education and Applied Linguistics Journal (EEAL Journal), 2025)
Participation in the classroom plays an important role because learning occurs through the interaction between the teacher and the students. However, many students do not participate in class, which can hinder effective communication and limit opportunities for collaborative learning. Then, one effective strategy to encourage participation is to pose questions to the students. This study aims to identify the types of questions most frequently used by the teacher and investigate the impact of these question types on fostering student participation in class. The data were collected through classroom observations and interviews consisting of a group of fourth-year students and one copywriting lecturer at an institution in the city of Garut. Observations were conducted just to determine what types of questions were frequently used by lecturers, followed by interviews to determine the impact of each type of question. The results of the observation showed that the most frequently used type of question was the closed type. Then from the interviews the researcher found that closed and convergent questions encouraged more participation because the questions could be answered briefly and more definitely. Recall questions and open questions reduced interest in participation because the questions require complex answers. Keywords: impact, interaction, participation, teacher questioning